Urokinase-Type Plasminogen Activator Deficiency Promotes Neoplasmatogenesis in the Colon of Mice()()() - Karamanavi, Elisavet (Neoplasia Press, 2014)
Urokinase-type plasminogen activator (uPA) participates in cancer-related biologic processes, such as wound healing and inflammation. The present study aimed to investigate the effect of uPA deficiency on the long-term outcome of early life episodes of dextran sodium sulfate (DSS)–induced colitis in mice. Wild-type (WT) and uPA-deficient (uPA(−/−)) BALB/c mice were treated with DSS or remained untreated. Mice were necropsied either 1 week or 7 months after DSS treatment. Colon samples were analyzed by histopathology, immunohistochemistry, ELISA, and real-time polymerase chain reaction. At 7 months, with no colitis evident, half of the uPA(−/−) mice had large colonic polypoid adenomas, whereas WT mice did not. One week after DSS treatment, there were typical DSS-induced colitis lesions in both WT and uPA(−/−) mice. The affected colon of uPA(−/−) mice, however, had features of delayed ulcer re-epithelialization and dysplastic lesions of higher grade developing on the basis of a significantly altered mucosal inflammatory milieu. The later was characterized by more neutrophils and macrophages, less regulatory T cells (Treg), significantly upregulated cytokines, including interleukin-6 (IL-6), IL-17, tumor necrosis factor-α, and IL-10, and lower levels of active transforming growth factor–β1 (TGF-β1) compared to WT mice. Dysfunctional Treg, more robust protumorigenic inflammatory events, and an inherited inability to produce adequate amounts of extracellular active TGF-β1 due to uPA deficiency are interlinked as probable explanations for the inflammatory-induced neoplasmatogenesis in the colon of uPA(−/−) mice.